Optimizing stability and characteristics of a vibrating rigid body pendulum with energy harvesting device - TS Amer; AM Wahba; AF Abolila; AA Galal (Journal of Low Frequency Noise, Vibration and Active Control)
The focus of this paper is on reducing vibrations and capturing energy from a three degrees-of-freedom (3DOF) dynamical system. The system consists of a damped spring-pendulum with an elliptical pivot path at a constant angular velocity and a connected rigid body experiencing external harmonic forces and moments. An independent electromagnetic energy harvesting system has been integrated into the structure, utilizing the motion of a magnet within a coil. The optimization efforts target both energy harvesting (EH) and vibration reduction capabilities. The second kind of Lagrange’s equations are used to formulate the governing kinematic equations, which are then solved asymptotically using the multiple-scales technique (MST), producing novel and precise results up to the third approximation. Various resonance cases are identified, with three examined concurrently. The time evolution of the solutions, as well as the modified phases and amplitudes, are analyzed through graphical representations, taking into account the influential parameters of the system. Graphical plots of phase portraits successfully depicted the system’s stable dynamics. The power output and current time profiles of the electromagnetic device are presented to demonstrate the impact of various parameters on system behavior. Analysis of stability and instability areas reveals that the system exhibits stable performance across a wide range of parameters. This model is gaining significance in contemporary applications, especially in control sensors used across various sectors such as industry, construction, automotive, transportation, and infrastructure.